Using a co-designed, self-delivered, Avatar-based patient discharge education application to improve acute coronary syndrome patient knowledge. (3rd October 2022) - Zhang, L; Gallagher, R; Du, H; Barry, T; Foote, J; Clark, R
Abstract: Background: 30-day rehospitalisation following heart event among acute coronary syndrome (ACS) patients remains high and is largely contributed by poor disease-related knowledge and self-management, especially in the disadvantaged patient groups such as those with low education levels and inadequate health literacy. Traditional patient education methods fail to address these issues. Purpose: This study aimed to test a unique consumer co-designed discharge education application (app) on patients' knowledge and its acceptability. Methods: ACS patients (unstable angina, non-STEMI or STEMI) were recruited from Royal Adelaide Hospital at South Australia during admission, provided with the app via tablet for one-month self-delivered education. The app has undergone a rigorous development process with the substantial engagement of consumers (Figure 1). App content includes the Heart Foundation Six Steps to Cardiac Recovery including disease-related knowledge, risk factor management, and ACS responses, assessed at baseline, followed by first use at discharge and one month later. Patients and cardiac nurses rated the acceptability of the app. Results: Among 22 Participants 81.8% were male (n=18), with a mean age of 59.7 (10.3) years, 45.5% (n=10) had not completed high school and nearly a quarter of the participants had marginal or below marginal health literacy. The diagnosis included STEMI (n=16, 72.7%) and non-STEMI (n=5, 22.7%). The majority of participants underwent percutaneous coronary intervention (PCI) (n=21, 95.5%) Significant improvements were observed for overall coronary artery disease knowledge at one month (p=0.003) and the exercise and nutrition domains at discharge (p=0.029; p<0.001) and one month (p=0.02; p=0.003) (Figure 2). Significant improvements were also observed for ACS knowledge and beliefs at discharge (p=0.008; p=0.038) and one month (p<0.001; p=0.025) when ACS response attitude was also significantly improved at one month (p=0.036). Overall acceptability was high at 7.7/10 (n=22 nurses) and 8.3/10 (patients). The participants described the app as `clear, simple, easy to understand, as well as stimulating and interactive, better than a live person'. Conclusion: This novel, self-delivered Avatar-based ACS discharge education App has the potential to provide discharge education for ACS patients even for those who have low education levels or inadequate health literacy. Results need to be confirmed in a randomised controlled trial. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): The National Heart Foundation Australia